Ultrathin and ultralong single-crystal platinum nanowire assemblies with highly stable electrocatalytic cctivity - Xia, Bao Yu (2013)
Ultrathin one-dimensional (1D) nanostructures such as nanowires and nanorods have drawn considerable attention due to their promising applications in various fields. Despite the numerous reports on 1D nanostructures of noble metals, one-pot solution synthesis of Pt 1D nanostructures still remains a great challenge, probably because of the intrinsic isotropic crystal growth behavior of Pt. Herein, we demonstrate the facile solvothermal synthesis of nanowire assemblies composed of ultrathin (ca. 3 nm) and ultralong (up to 10 μm) Pt nanowires without involving any template. The oriented attachment mechanism is found to be partially responsible for the formation of such ultrathin Pt nanowires. The amine molecules generated during the reaction might assist the formation of nanowire assemblies. Importantly, the present system can be extended to synthesize Pt-based alloy nanowire assemblies such as Pt–Au and Pt–Pd. These Pt nanowires can be easily cast into a free-standing membrane, which exhibits excellent electrocatalytic activity and very high stability for formic acid and methanol oxidation and the oxygen reduction reaction.